Release of non-extractable or bound residues of the atrazine herbicide in soil and its absorption by plants - Nakagawa, Lia Emi; Andréa, Maria Mercedes de (Pesquisa Agropecuaria Brasileira, 2000)
Among the pesticide residues in soil, the non-extractable or bound residues may be formed resulting in less bioavailability and less leaching of the pesticide residues. From the environmental point of view the knowledge on the possibility of the biorelease of these residues is needed for evaluations on long term pollution. The release of 14C-atrazine bound residues was investigated in soil by addition of inocula with microorganisms and the possibility of their absorption by plants through radiometric techniques. The 14CO2 production almost did not happen (only from 0% to 0.8%) and additional release of extractable residue from bound residues of 14C-atrazine was small (until 3.5%). The bioreleased values were near the same in sterilized or with inocula of microorganisms soil samples. The uptake of bound residues was not observed neither by rice or bean plants.